Design of an automated hybrid system for aquaculture and agriculture process and its performance analysis - Wahid, Herman; Mohd Noor, Ahmad Fakri; Burhanuddin, Dirman Hanafi; Ghazali, Rozaimi (UTHM Publisher, 2017)
Fish farming (aquaculture) has become one of important food resources in human life. With the high demand of fish in the market, the fish farmer is forced to find the alternatives way to increase the fish farming production. The use of cement pond, land pond, canvas pond etc. will cause some obstacles to the fish. The ammonia is one of the waste produced from the fish manure and the feed waste. The increasing of ammonia inside the aquaculture system will lead to fish life interruption or death. Nevertheless, ammonia that is converted to nitrate has good potential for the growths of plants in agriculture system. This study aims to provide the solution of the stated problems by pumping the ammonia-contained water to the agriculture by applying an automation system. The water which is going through to the plants can isolate the ammonia and filter the good quality water back to the fish pond. To reduce the system cost, pH sensor is used as an alternative way to represent the ammonia level in the aquaculture system. Besides, the system will be operated in a power-saving mode where the water pump will not be operated if the amount of ammonia does not exceed the limit. Hence, water pump will operate twice a day by scheduling it using a microcontroller in order to ensure the plant will receive the suitable amount of ammonia water for growing. Besides, the development of auto fish feeder is another added feature for this system.